2015
DOI: 10.1136/jclinpath-2015-203281
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of formalin and GEWF in fixation of colorectal carcinoma specimens: rates of lymph node retrieval and effect on TNM staging

Abstract: The routine use of adjunct techniques to identify additional lymph nodes is unnecessary with underlying high-quality dissection practice. Emphasis should be placed upon education and training, spending appropriate time dissecting and ensuring specimens are sufficiently fixed beforehand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…A total number of 432 studies were identified, 15 of which RCTs [14][15][16][17][18][24][25][26][27][28][29][30][31][32][33] with a total of 1445 specimens fulfilled the inclusion criteria (Figure 1). Randomised studies reporting on gastric malignancies were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…A total number of 432 studies were identified, 15 of which RCTs [14][15][16][17][18][24][25][26][27][28][29][30][31][32][33] with a total of 1445 specimens fulfilled the inclusion criteria (Figure 1). Randomised studies reporting on gastric malignancies were excluded.…”
Section: Resultsmentioning
confidence: 99%
“…A further study from this group demonstrated the importance of detecting small (<5 mm diameter) nodes and the effect of systematic fat blocking on nodal stage. A recent prospective controlled study in colorectal specimens showed that extended fixation and a lymph node revealing solution increased node yield but did not result in upstaging 13. The authors concluded that high-quality dissection practice obviated the need for lymph node revealing techniques.…”
Section: Discussionmentioning
confidence: 99%
“…However, this is not an easy task, and finding small LNs may be challenging. Fat clearing solutions have been proposed to facilitate the detection of LNs 7 , 10 , 11 , 12 . A clear benefit is seen when LN count is low 11 , 12 , but apparently the impact is reduced or absent if the LN yield is high 7 , 10 .…”
Section: Discussionmentioning
confidence: 99%
“…Fat clearing solutions have been proposed to facilitate the detection of LNs 7 , 10 , 11 , 12 . A clear benefit is seen when LN count is low 11 , 12 , but apparently the impact is reduced or absent if the LN yield is high 7 , 10 . CS is a validated and inexpensive tissue fixative that improves detection and staging accuracy of LN in rectal cancer following chemotherapy 14 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation